Oceans of Discourses: Utilizing Q Methodology for Analyzing Perceptions on Marine Biodiversity Conservation in the Kogelberg Biosphere Reserve, South Africa - Hagan, Kristin; Williams, Samantha (Frontiers in Marine Science, 2016)
This paper attempts to empirically investigate perceptions regarding marine biodiversity conservation among different stakeholders of the Kogelberg Biosphere Reserve, South Africa. The study’s data was collected by following Q methodology in combination with semi-structured interviews and participant observation. Q methodology combines elements from quantitative and qualitative research traditions, providing researchers with a systematic and rigorous means to study human subjectivities. Primary data were gathered from stakeholders who either live, work, or have performed research in the Kogelberg Biosphere Reserve. A combination of interpretative discourse analysis and Q factor analysis was employed to identify perceptions. The results reveal that there are two operating discourses with clear stakeholder divisions. The science discourse is characterized by its scientific management-based ecological approach. On the other hand, the livelihoods discourse is primarily concerned about the social implications brought about by Kogelberg as a biosphere reserve. The paper goes on to argue that the meaning people attach to the concept of ‘marine biodiversity conservation’ is relational as it is based on their lived experience. It further highlights the importance of performing context-specific social research of protected areas, as it is difficult for conservation projects to meet both ecological and social needs without understanding the viewpoints of engaged stakeholders and local communities.